The toxic effect of rhodamine B in rats - G. Nainggolan Sihombing (Indonesian Pediatric Society, 1984)
A multigeneration rat feeding study was carried out with rhodamine B incorporated in the usual stockdiet [or albino rats. Rhodamine B is a red inedible synthetic dyestuff wrongly but widely used in Jakarta for colouring cheap snacks and drinks prepared at the homelevel and sold by streetvendors. Under the conditions of the experiment the main findings observed were : 1) retardation of growth, starting from birth to adulthood 2) decrease in reproductive ability as seen from continuing decrease of littersize with each following generation 3) behavioral changes of adult rats, such as itching, irritability, aggressiveness and cannibalism 4) increased susceptibility to infection (respiratory diseases) in adult rats resulting in decreased longevity 5) development of tumors in the lymphnodes. The purpose of this investigation is through reporting the findings to awake renewed interest on the part of the authority for the problem of provision of the so badly needed cheap but edible foodgrade colours for the less privileged members of the society.